$$(g-2)_{e,μ }$$ ( g - 2 ) e , μ and lepton flavor violating decays in a left-right model - L. T. Hue; Khiem Hong Phan; T. T. Hong; T. Phong Nguyen; N. H. T. Nha (European Physical Journal C: Particles and Fields)
Abstract General expressions for one-loop contributions associated with lepton-flavor violating decays of the standard model-like Higgs boson $$h→ e_b^± e_a^\mp $$ h → e b ± e a ∓ and gauge boson $$Z→ e^± _b e_a^\mp $$ Z → e b ± e a ∓ are introduced in the unitary gauge. The results are used to discuss these decays as new physics signals in a minimal left-right symmetric model containing only one bidoublet Higgs and a $$SU(2)_R$$ S U ( 2 ) R Higgs doublet accommodating data of neutrino oscillations and $$(g-2)_{μ }$$ ( g - 2 ) μ . The numerical investigation indicates that some of these decay rates can reach near future experimental sensitivities.